Avaliação do tempo de vida útil de biodiesel metílico obtido a partir da mistura de sebo bovino e óleos de soja e babaçu - Teixeira, Geuza Araújo de Albuquerque (2010)
This study evaluates biodiesel samples produced from mixtures of beef tallow, babassu oil and soybean oil at four different ratios, by transesterification using methyl alcohol and basic catalysis, seeking to explain its oxidative stability during storage for 180 days. The biodiesel synthesis in methylic route was processed under conditions of oil-alcohol molar ratio of 1:6 (m/m), 1.5% KOH, 50°C. After the methoxide addition the bath was turned off. The results on the physical-chemical properties of biodiesel samples have met the limits set by the technical regulation No. 7 of the National Agency for Oil, Natural Gas and Biofuels. By gas chromatography it was possible to identify the fatty acids mixtures and their esters. Thermal study of the mixtures, in oxidizing atmospheres (synthetic air and oxygen), shows three stages of thermal decomposition, and for biodiesel samples, under the same analysis conditions, there are two steps. The first step can be attributed to the volatilization of fatty acid esters, as well as the loss of volatile compounds formed by oxidation process, and the second step can be attributed to the polymers combustion formed during the analysis. The TMDSC curves of biodiesel samples, shows crystallization temperatures very close to those found in PEFF. It is also observed in the thermograms that the biodiesel samples are more volatile in relation to mixtures. The biodiesel fuel samples produced satisfactory combustion properties. The storage study of biodiesel samples in the period of 180 days showed results of specific mass (20ºC), viscosity (40°C), cold flow plugging point (CFPP) and acidity index within specifications. Biodiesel 1 showed the oxidation induction time lower than that prescribed. Since the water content found for all biodiesel samples showed values above the set. Nevertheless the samples of biodiesel made from mixtures of oils and animal fats can be applied as fuel.